High Interest in Pursuing Trauma-Informed Care in Nursing Home Social Services Directors. (July 2023) - Kusmaul, Nancy; Becker, Todd D.; Hector, Paige; Bern-Klug, Mercedes; Smith, Kevin M.
This study explored nursing home social services directors' interest in pursuing trauma-informed care (TIC) training, and individual and organizational characteristics associated with their interest. Data from the 2019 National Nursing Home Social Services Directors Survey, a national cross-sectional survey, were used. Measures sought information on participants' interest in TIC training, sociodemographic characteristics, and characteristics of employing nursing homes. Descriptive statistics and multivariate binary logistic regression analyses were used. Of the 924 respondents, 880 (95.2%) were included in the analysis. Most (71.7%) expressed high interest in TIC training. Younger age, fewer years of nursing home social services experience, being degreed and licensed in social work, and being a person of color were associated with greater odds of high interest in TIC training. Neither nursing home ownership nor social services staffing ratio was significantly associated with interest in TIC training. As policy requires TIC in nursing homes, these findings present a first step towards understanding implementation.